Exacerbation of Pulmonic Regurgitation by Diastolic Tricuspid Regurgitation. Issue 8 (4th July 2014) - Fan, Dali; Makaryus, John N.; Wassef, Bishoy; Suma, Valentin; Masry, Mina; Makaryus, Amgad N.
<x xml:space="preserve">Abstract</x> Few cases of diastolic mitral regurgitation (MR) and tricuspid regurgitation (TR) have been reported in the world literature. We report the case of a 63‐year‐old woman admitted for syncope, with a permanent pacemaker following complete heart block. Echocardiography revealed that the timing of the diastolic TR (and noted MR) coincided with the second phase of the pulmonic insufficiency (PI) jet. The respirometer revealed that the diastolic TR and the second phase of the PI are highly sensitive to respiration (attenuated with inspiration and exacerbated with expiration). The uniqueness of this case is the rare occurrence of the exacerbation of PI as the result of diastolic TR.